2011
DOI: 10.3109/19396368.2010.500440
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution exposure and damage to male gametes: human studies andin situ‘sentinel’ animal experiments

Abstract: Globally there is concern that adverse reproductive outcomes and fertility impairment in humans may be caused by exposure to environmental contaminants. Air pollution in particular has been linked to DNA damage, abnormal sperm morphology, and reduced sperm performance in men. Experimental studies using model species (mice and rats) exposed in situ provide evidence that ambient air pollution can cause damage to the respiratory system and other tissues or organs. This can take the form of DNA damage and other ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 77 publications
0
29
0
2
Order By: Relevance
“…b There are two studies, both in mice [Yauk et al, 2007;Marchetti et al, 2011]. These agents induce similar biomarker effects in humans as they do in animals, such as DNA damage in sperm, as reviewed for ionizing radiation and chemotherapy [Kamiguchi and Tateno, 2002], smoking [DeMarini, 2004], and air pollution [Somers, 2011]. Thus, there is sufficiently strong mechanistic evidence for how these agents affect animals and humans.…”
Section: Need For a Declaration Panel And Implications Of Declaring Amentioning
confidence: 99%
See 1 more Smart Citation
“…b There are two studies, both in mice [Yauk et al, 2007;Marchetti et al, 2011]. These agents induce similar biomarker effects in humans as they do in animals, such as DNA damage in sperm, as reviewed for ionizing radiation and chemotherapy [Kamiguchi and Tateno, 2002], smoking [DeMarini, 2004], and air pollution [Somers, 2011]. Thus, there is sufficiently strong mechanistic evidence for how these agents affect animals and humans.…”
Section: Need For a Declaration Panel And Implications Of Declaring Amentioning
confidence: 99%
“…Of 48 agents evaluated for induction of germ-cell mutations in rodents, 39 of them are positive [Shelby 1996;Witt and Bishop, 1996;Russell, 2004;Marchetti and Wyrobek 2005;Glen et al, 2008;Marchetti et al, 2011;Somers, 2011]. The published rodent germ-cell mutagens include ionizing radiation; cancer chemotherapy agents; food components (acrylamide); environmental contaminants (benzo[a]pyrene); and common complex mixtures to which nearly everyone is exposed, such as main-and side-stream tobacco smoke, diesel exhaust, and the particulate fraction of air pollution [Yauk et al, 2007;Marchetti et al, 2011;Ritz et al, 2011;Somers, 2011]. Table I illustrates that some of these agents are carcinogenic and somatic-cell mutagens in both humans and rodents, as well as germ-cell mutagens in rodents.…”
Section: Possible Human Germ-cell Mutagensmentioning
confidence: 99%
“…Epidemiological studies demonstrated exposure to ambient levels of air pollutants, especially airborne particulate matter, has been linked in particular to DNA fragmentation (Selevan et al, 2000) (Evenson et al, 2005) and in general to abnormal sperm morphology and reduced sperm performance in men. (Somers 2011;Hammoud et al, 2010). Recent experimental animal data indicated that female fertility is also affected by air pollutants (Veras et al, 2010).…”
Section: Infertilitymentioning
confidence: 99%
“…Perhaps this level of DNA damage can be tolerated. The association with the birth of the healthy child is not yet known although animal studies appear to be leading the way (reviewed in Somers 2011]). However, the long-term consequences remain unknown.…”
Section: Air Pollutantsmentioning
confidence: 99%